Получение и моделирование сверхтвердой фазы из фуллеренов в металлической матрице - Черногорова, О.П.; Дроздова, Е.И.; Бульенков, Н.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
The synthesis of superhard phases (SHP) from fullerenes С₆₀+С₇₀ mixed with metal powders occurs at a relatively low pressure (3-5 GPa) and allows one to obtain large SHP particles (up to 0.5 mm) with a rather perfect aperiodic structure. The examination of the SHP structure by highresolution electron microscopy showed the presence of locally ordered zones with a pseudohexagonal structure, although these particles are X-ray amorphous. Such structure can be considered as the nanocomposite formed by the zones of almost crystalline structure (approximants) with the intermediate regions of less ordered structure. The structures of such crystalline approximants were modeled by the method of modular design. A version of such approximants has a hexagonal lattice, and all С₆₀ molecules are joined by sp³ bonds only along the fivefold symmetry axes.